Pengaruh Karakteristik Petani pada Persepsi Petani dalam Pengembangan Agrowisata “Bon Deso”, Kota Batu - Pravasta Wahyu Satriawan; Sugiyanto Sugiyanto; Asihing Kustanti; Budi Sawitri (Institut Pertanian Bogor, 2024)
Developing strategic land use issues into agrotourism is increasingly prevalent in Batu City. This condition raises various kinds of farmers' perceptions about who feels the benefits of the presence of tourism. Various backgrounds make these differences in perception even more visible. This study aims to analyze the influence of farmers' characteristics on their perceptions of developing